Risk evaluation of metformin use in patients with kidney injury. - José Paulo Marques Souto (2020)
Background: In a world where the prevalence of Diabetes is ever increasing metformin plays an important role in the management of the disease. The most feared adverse effect of metformin is lactic acidosis, a rare situation that has a poor prognosis. This study aims to report the cases of metformin associated lactic acidosis (MALA) in Centro Hospitalar Universitário de São João (CHUSJ) evaluated by the Nephrology department. Methods: All cases of MALA in diabetic patients admitted to our tertiary center that had an evaluation by the nephrology department from the year of 2017 until 2019 were included. Data referring to clinical status, blood analysis, evolution and outcome were retrospectively analyzed. Results: We identified 10 patients with MALA and verified only 1 death, which wasn't directly attributable to this condition. At admission patients presented with arterial blood pH of 7.07 ± 0.14 and plasma lactate of 9.67 ± 4.09. There was no significant association between days of hospitalization and either pH, plasma creatinine or lactate at admission. Conclusion: MALA diagnostic and metformin's association with lactic acidosis remains not completely clarified. Our study shows lower mortality than what has been previously published. To date, no reliable predictor of mortality has been identified. More studies are needed to evaluate the usefulness of determining metformin concentrations and to assess the true influence of the drug in the development of lactic acidosis.